Transcriptional regulation of miR528-PPO module by miR156 targeted SPLs orchestrates chilling response in banana - Xiangjin Kong; Kuan Peng; Youxia Shan; Ze Yun; Tamas Dalmay; Xuewu Duan; Yueming Jiang; Hongxia Qu; Hong Zhu (Molecular Horticulture)
Abstract Banana is sensitive to cold stress and often suffers from chilling injury with browning peel and failure to normal ripening. We have previously reported that banana chilling injury is accompanied by a reduction of miR528 accumulation, alleviating the degradation of its target gene MaPPO and raising ROS levels that cause peel browning. Here, we further revealed that the miR528-MaPPO cold-responsive module was regulated by miR156-targeted SPL transcription factors, and the miR156c-MaSPL4 module was also responsive to cold stress in banana. Transient overexpression of miR156c resulted in a more severe chilling phenotype by decreasing the expression of MaSPL4 and miR528. Conversely, the browning was alleviated in STTM-miR156c silencing and OE-MaSPL4 samples. Furthermore, DNA affinity purification sequencing and MaSPL4-overexpressing transcriptome jointly revealed that MaSPL4 may mediate the transcription of genes related to lipid metabolism and antioxidation, in addition to the miR528-MaPPO module, demonstrating MaSPL4 as a master regulator in the fruit cold response network. In summary, our results suggest that the miR156c-MaSPL4 module can mediate the chilling response in banana by regulating the miR528-MaPPO module and multiple other pathways, which provides evidence for the crosstalk between TFs and miRNAs that can be used for the molecular breeding of fruit cold tolerance.